Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1371/journal.pone.0238219
|View full text |Cite
|
Sign up to set email alerts
|

Ground-dwelling arthropods of pinyon-juniper woodlands: Arthropod community patterns are driven by climate and overall plant productivity, not host tree species

Abstract: Pinyon-juniper (PJ) woodlands have drastically changed over the last century with juniper encroaching into adjacent habitats and pinyon experiencing large-scale mortality events from drought. Changes in climate and forest composition may pose challenges for animal communities found in PJ woodlands, especially if animals specialize on tree species sensitive to drought. Here we test habitat specialization of ground-dwelling arthropod (GDA) communities underneath pinyon and juniper trees. We also investigate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Other climatic and geographic factors, like temperature, pressure, geology and rainfall are also important. This analysis is highly consistent with Uhey et al, (2020), who reported a positive correlation of NDVI with elevation.…”
Section: Variation Of Ndvi With Elevationsupporting
confidence: 91%
“…Other climatic and geographic factors, like temperature, pressure, geology and rainfall are also important. This analysis is highly consistent with Uhey et al, (2020), who reported a positive correlation of NDVI with elevation.…”
Section: Variation Of Ndvi With Elevationsupporting
confidence: 91%
“…In contrast, long-term temperature data with a spatial resolution of 1 km × 1 km explained very low amounts of variation. Arthropod community composition is known to respond to long-term climate (Zellweger et al 2017 ; Uhey et al 2020 ) as well as to local-scale temperatures (Prather and Kaspari 2019 ; Uhler et al 2021 ). Plant species composition summarizes fine-scale microclimatic patterns for any desired area (here, 200-m buffer areas around the Malaise traps) and worked as a better proxy of local climatic conditions in our case.…”
Section: Discussionmentioning
confidence: 99%
“…Arthropods strongly respond to climatic conditions such as temperature, since they are ectothermic organisms (Chown and Nicolson 2004 ; Angilletta 2009 ). Several studies emphasized climate as a key driver of arthropod communities, reporting significant changes in species composition along gradients of temperature and precipitation (Lessard et al 2011 ; Uhey et al 2020 ). In addition, responses of arthropods to climate can indirectly be driven by temperature ranges of other organisms such as host plants (Hodkinson 2005 ), or microclimatic effects mediated by vegetation structure (Suggitt et al 2011 ; Prather and Kaspari 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Given that arthropods are known to be active mostly during the warmer months (Mavasa et al 2022) and have been reported to correlate positively with precipitation (Uhey et al 2020), we sampled in October 2021. Since the study was focused on surface-active arthropods, the pitfall trapping method was used.…”
Section: Collection and Identification Of Surface-active Arthropodsmentioning
confidence: 99%